Identifying attendance patterns in a smoking cessation treatment and their relationships with quit success. (1st May 2017) - Jacquart, Jolene; Papini, Santiago; Davis, Michelle L.; Rosenfield, David; Powers, Mark B.; Frierson, Georita M.; Hopkins, Lindsey B.; Baird, Scarlett O.; Marcus, Bess H.; Church, Timothy S.; Otto, Michael W.; Zvolensky, Michael J.; et al.
Highlights: Attendance was characterized by three patterns; Completers, Titrators, and Droppers. Titration was associated with lower quit success within the control condition. Titrators and Completers had similar quit success within the exercise intervention. Abstract: Background: While important for substance use outcomes, knowledge about treatment attendance patterns, and their relation with clinical outcomes is limited. We examined the association between attendance patterns and smoking outcomes in a randomized, controlled smoking cessation intervention trial. Methods: In addition to standard smoking cessation treatment, participants were randomized to 15 weeks of an exercise intervention (n = 72) or an education control condition (n = 64). Latent class growth analysis (LCGA) tested whether intervention attendance would be better modeled as qualitatively distinct attendance patterns rather than as a single mean pattern. Multivariate generalized linear mixed modeling (GLMM) was used to evaluate associations between the attendance patterns and abstinence at the end of treatment and at 6-month follow-up. Results: The LCGA solution with three patterns characterized by high probability of attendance throughout (Completers, 46.3%), gradual decreasing probability of attendance (Titrators, 23.5%), and high probability of dropout within the first few weeks (Droppers, 30.1%) provided the best fit. The GLMM analysis indicated an interaction of attendance pattern by treatment condition, such that titration was associated with lower probability of quit success for those in the control condition. Probability of quit success was not significantly different between Titrators and Completers in the exercise condition. Conclusions: These findings underscore the importance of examining how treatment efficacy may vary as a function of attendance patterns. Importantly, treatment discontinuation is not necessarily indicative of poorer abstinence outcome.